Phase resonances induced by a subwavelength particle near a surface with two cavities - Valencia, Claudio (2015)
It is well known that finite groove gratings with subwavelength features exhibit phase resonances, which are associated with a particular distribution of the magnetic field phase within the cavities and are characterized by a significant enhancement of the internal field. For a flat surface with identical grooves under symmetrical conditions of incidence, it was shown that a minimum of three cavities is required to excite a phase resonance. In this paper we show that by approaching a particle to the surface, this requirement is removed and the particle enables the excitation of phase resonances even in a system of two identical cavities under normal incidence. The influence of the position and the radius of the particle in the reflected far field response, as well as in the near and internal field, is analyzed. The possibility of exciting phase resonances in this system opens up new means for the design of sensing devices.